The role of innovation in mediating the relationship between entrepreneurial orientation and digital literacy on sustainability performance: A study of developing tourism villages in Jembrana Regency - Dewi, Ni Made Rai Christina Kusuma; Sukawati, Tjokorda Gde Raka; Sukaatmadja, I Putu Gde; Rahanatha, Gede Bayu (International research journal of management, IT and social sciences, 2025)
This study examines the relationships among entrepreneurial orientation, digital literacy, innovation, and sustainability performance in Jembrana's developing tourist villages. Focusing on how entrepreneurial mindset and digital skills directly influence sustainability, and how innovation mediates these effects, the research addresses the concept of sustainability across economic, social, environmental, and technology dimensions. Conducted in Blimbingsari and Ekasari tourist villages, the study surveyed 170 respondents using a quantitative approach with Structural Equation Modelling–Partial Least Squares (SEM-PLS) analysis. Findings indicate that entrepreneurial orientation, digital literacy, and innovation have a significant and positive impact on sustainability performance. Additionally, both entrepreneurial orientation and digital literacy significantly and positively influence innovation. The findings are expected to contribute to the development of tourism villages in Jembrana Regency through strengthening entrepreneurial orientation, improving digital literacy, and implementing innovation. The practical implications of this research encourage tourism village managers in Jembrana Regency to focus on increasing their willingness to take risks in exploring new development opportunities, enhancing innovation in marketing activities, and improving knowledge in digital content creation.